Pengaruh Variasi Parameter Waktu Gesek Dan Jarak Penekanan Terhadap Kekuatan Impak Sambungan Hasil Friction Welding Pada Baja AISI 4140 - Tresnov Switella, Argona; Rodika, Rodika; Rivai, Muhammad (Jurnal Inovasi Teknologi Terapan, 2023)
Friction welding is a welding technique that uses heat generated by friction, and this concept works on the surfaces of two materials that are in contact, namely rotating while the other is stationary and applying a compressive force at the same speed to provide heat to melt one metal into another. This study aimed to determine the effect of friction time and pressure distance variations on impact strength in the friction welding process of AISI 4140 steel. A solid cylinder having Ø 20 mm. So, this research will be carried out using the experimental method; it is found that friction welding using 90 seconds and a pressure distance of 4 mm produces an average absorbed impact energy of 31.31 joules and an average impact price of 0.05692 joules/mm2 and for the lowest value, namely at 60 seconds and the pressure distance is 2 mm with the average value of the impact absorbed is 6.44 joules. The average impact price is 0.01168 Joule/mm2. Because the longer the friction time and the pressure distance, the results of the friction welding better.